Biological control potential of worrisome wheat blast disease by the seed endophytic bacilli - Surovy, Musrat Zahan; Dutta, Sudipta; Mahmud, Nur Uddin; Gupta, Dipali Rani; Farhana, Tarin; Paul, Sanjay Kumar; Win, Joe; Dunlap, Christopher; Oliva, Ricardo; Rahman, Mahfuzur; Sharpe, Andrew G.; Islam, Tofazzal (Frontiers in Microbiology, 2024)
Crop production often faces challenges from plant diseases, and biological control emerges as an effective, environmentally friendly, cost-effective, and sustainable alternative to chemical control.Wheat blast disease caused by fungal pathogen Magnaporthe oryzae Triticum (MoT), is a potential catastrophic threat to global food security. This study aimed to identify potential bacterial isolates from rice and wheat seeds with inhibitory effects against MoT. In dual culture and seedling assays, three bacterial isolates (BTS-3, BTS-4, and BTLK6A) demonstrated effective suppression of MoT growth and reduced wheat blast severity when artificially inoculated at the seedling stage. Genome phylogeny identified these isolates as Bacillus subtilis (BTS-3) and B. velezensis (BTS-4 and BTLK6A). Whole-genome analysis revealed the presence of genes responsible for controlling MoT through antimicrobial defense, antioxidant defense, cell wall degradation, and induced systemic resistance (ISR). Taken together, our results suggest that the suppression of wheat blast disease by seed endophytic B. subtilis (BTS-3) and B. velezensis (BTS-4 and BTLK6A) is liked with antibiosis and induced systemic resistance to wheat plants. A further field validation is needed before recommending these endophytic bacteria for biological control of wheat blast.